Grass-plastic composite material and preparation method thereof
Through the combination of rape straw rind powder and bamboo chip powder and hot-mixing machine mixing hot pressing technology, combined with polymer and magnesium sulfide cement, the ratio of composite foaming agent and the extrusion forming temperature are optimized, and the problems of poor mechanical properties and poor water resistance of Hepu composite materials are solved, and the Hepu composite materials with high mechanical properties and good water resistance are achieved.
Patent Information
- Application Number
- CN202411895761.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
The existing Hemoplastic composites have problems with poor mechanical properties and poor water resistance.
Through the combination of rape straw rind powder and bamboo chip powder, combined with polymer and magnesium sulfide cement, the mixing and hot pressing technology of a hot mixer is used to adjust the proportion of composite foaming agent and the extrusion forming temperature to optimize the cell structure.
The load bearing capacity, rigidity, bending strength and bending resistance of Hepu composite materials are significantly improved, their uniformity and orderliness are enhanced, their tensile strength, tensile modulus and tensile performance are improved, and water resistance is improved.
Smart Images

Figure CN119639064A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, in particular to a grass-plastic composite material and a preparation method thereof. Background Art
[0002] Hesu composite is a new type of wood-like material, which is made by mixing industrial waste such as straw, bagasse, reed or bamboo chips with thermoplastic resins such as polypropylene, polyethylene, polyvinyl chloride, etc. It combines the advantages of wood and plastic, and exhibits high mechanical properties and strong water resistance that surpass wood materials. It has broad market prospects.
[0003] Bamboo chips and rapeseed straw powder are by-products of the processing of bamboo tubes and rapeseed respectively. If they can be effectively utilized, they can not only reduce carbon emissions, but also reduce the energy consumption of building materials in the production stage, and can also fix carbon and reduce carbon dioxide emissions. Bamboo chips and rapeseed straw powder waste are used as filling materials, and polymers and other materials are added to modify them. The resulting grass-plastic composites can be widely used in the fields of furniture decoration materials, etc., with multiple meanings such as being green, economical, pressure-resistant and waterproof.
[0004] Chinese patent CN101880464B discloses a bamboo-based / thermoplastic nanocomposite material. The invention improves the interface compatibility between the fiber and the thermoplastic by adding nanoparticles to fill the bamboo fiber, thereby improving the physical and mechanical strength and interface compatibility of the composite material. However, the invention adds 55-60% bamboo fiber, and the bamboo fiber particle size is 200 mesh, resulting in too many large-sized plant fibers inside the material, increasing the internal voids of the material, and enhancing the water absorption of the composite material prepared therefrom, and having poor water resistance.
[0005] Chinese patent CN116218247B discloses a porous wood-plastic composite material and a preparation method thereof. The composite material prepared by the invention using modified casting solid waste, wood solid waste and low-density polyethylene has good rigidity and thermal stability; however, since 60-80% of the raw materials used in the invention are wood solid waste and low-density polyethylene, the prepared composite material has strong water absorption, is easy to swell, decay and deform, and has huge hidden dangers in terms of water resistance and mechanical properties.
[0006] In summary, the existing Hesu composites have the problems of poor mechanical properties and poor water resistance.
[0007] Therefore, a grass-plastic composite material and a preparation method thereof are proposed. Summary of the invention
[0008] The object of the present invention is to provide a grass-plastic composite and a preparation method thereof. By compounding rape straw husk powder and bamboo chip powder, the load bearing capacity, rigidity, bending strength and bending resistance of the grass-plastic composite are significantly improved; at the same time, the uniformity and orderliness of the grass-plastic composite are improved, the tensile strength and tensile modulus are increased, and the tensile resistance is further improved; by adjusting the ratio of MgO and MgSO4 in magnesium oxysulfate cement, the density of the grass-plastic composite and the compactness of the internal structure are enhanced, and the axial tensile mechanical properties are further improved; by improving the preparation process and the extrusion molding process, adjusting the ratio of the composite foaming agent and the extrusion molding temperature, the pore structure of the grass-plastic composite is optimized, and the prepared grass-plastic composite has the characteristics of high mechanical properties and good water resistance.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] In one aspect, the present invention provides a method for preparing a ramie-plastic composite material, and the preparation method is as follows:
[0011] The crusher is used to simply crush bamboo chips and rape straw to obtain crushed bamboo chips and crushed rape straw with a size of 1 cm; the crushed rape straw husk and the crushed rape straw pith in the crushed rape straw are separated by a density separator with a suction head speed of 2.1-6.4 mm / sec and a rotation speed of 20-60 rpm; the crushed rape straw husk and the crushed bamboo chips are crushed again, and sieved to obtain bamboo chip powder and rape straw husk powder with a mesh number of 60-100 meshes.
[0012] Bamboo dust powder and rape straw husk powder are added to a hot mixer with a mass ratio of 50-70:30-50 together with a polymer and magnesium oxysulfide cement, and stirred for 10 minutes to obtain a mixed material; a coupling agent and 2-6 parts of a calcium carbonate nucleating agent are added to the mixed material, and the mixed material is mixed and hot pressed by utilizing the high-speed rotation friction heat generated by the hot mixer, and mixed at a speed of 2500 r / min and a temperature of 85°C for 10 minutes to obtain a modified composite material.
[0013] 100 portions of the modified composite material are put into a hot-pressing extruder, and a composite foaming agent and water are added as auxiliary agents for hot pressing for 5 minutes at 175°C and 1-3MPa; the temperature of the extruder barrel in the transition body and the die zone I is 175-220°C to obtain a primary material; the temperature in the die zone II is reduced from 195°C to 140-160°C to prepare a Hesu composite; the mass ratio of the endothermic foaming agent to the exothermic foaming agent in the composite foaming agent is 3-5:1; the endothermic foaming agent is sodium bicarbonate; the exothermic foaming agent is azodicarbonamide; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite.
[0014] Preferably, the pretreatment process of bamboo dust powder and rape straw husk powder is as follows: using a crusher to simply crush bamboo dust and rape straw to obtain crushed bamboo dust and crushed rape straw with a size of 1 cm; sending the crushed rape straw into a density separator, adjusting the suction head speed and rotation speed of the density separator to separate the crushed rape straw pith with a smaller density from the crushed rape straw husk with a larger density; using a high-speed pulverizer to crush the separated crushed rape straw husk and crushed bamboo dust again, sieving them, and then putting them into a 110°C drying oven to dry to constant weight, to obtain bamboo dust powder with a mesh size of 60-100 mesh and the rape straw husk powder.
[0015] Preferably, the suction head speed of the density separator is 4.2-6.4 mm / sec, and the rotation speed is 40-60 rpm; the sieving mesh number of the bamboo scraps powder and the rape straw husk powder is 80-100 mesh.
[0016] Preferably, the polymer is any one of ethylene-ethyl acrylate copolymer, high-density polyethylene, polypropylene, and polyvinyl chloride.
[0017] Preferably, the mass ratio of bamboo chip powder to rape straw husk powder is 50-60:40-50.
[0018] Preferably, the preparation method of magnesium oxysulfate cement is: stirring MgSO4 and H2O in a molar ratio of 1:20 and slowly adding H2SO4 with a purity of 98% to dissolve to obtain a mixture one, adding MgO to the mixture one, the molar ratio of the added MgO to MgSO4 being 8-10:1, and continuing stirring for 5 minutes to obtain magnesium oxysulfate cement.
[0019] Preferably, the preparation method of the mixed material is: adding bamboo dust powder and rape straw husk powder in a mass ratio of 60:40 together with 100 parts of polymer and 0.3 parts of magnesium oxysulfate cement into a hot mixer, adjusting the speed of the hot mixer to 500 r / min and the temperature to 85°C, and fully mixing and stirring for 10 minutes to achieve melting of the polymer, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material.
[0020] Preferably, the coupling agent is any one of the silane coupling agent γ-aminopropyltriethoxysilane, the titanate coupling agent tetraisopropyl titanate, and the monoalkoxyaluminate Konalink 101.
[0021] Preferably, the preparation method of the Hesu composite is as follows: take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder, add 5% of a composite foaming agent under the conditions of 175°C, a rotation speed of 400r / min, and a pressure of 1MPa, wherein the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 3:1; then add 3% of water as an auxiliary agent and hot press for 5 minutes; the temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 220°C to fully foam it to obtain the initial material; the temperature in the die zone II is reduced from 195°C to 140°C to prepare the Hesu composite.
[0022] On the other hand, the present invention provides a grass-plastic composite material, which includes a modified composite material and a composite foaming agent; the modified composite material includes a mixed material, a coupling agent and a calcium carbonate nucleating agent; the composite foaming agent includes an endothermic foaming agent sodium bicarbonate and an exothermic foaming agent azodicarbonamide; the mixed material includes bamboo dust powder, rape straw husk powder, a polymer and magnesium oxysulfate cement; the magnesium oxysulfate cement includes MgO, MgSO4, H2O and H2SO4; the grass-plastic composite material is prepared by any one of the above preparation methods.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The pith and skin of rape straw are fully separated through a density separator, and bamboo powder and rape straw skin powder are compounded through particle size screening. The obtained mixed material has better load-bearing ability and forms a supporting network in the rice-plastic composite, which increases the interface compatibility between materials and enhances the overall rigidity of the rice-plastic composite. At the same time, the friction and contact area inside the material also increase accordingly, resulting in an increase in the viscosity of the system. A criss-cross skeleton structure is formed inside the rice-plastic composite, the internal connection of the material is tighter, and the ability to resist bending deformation is stronger. The prepared rice-plastic composite has higher bending strength and bending modulus, which improves its bending resistance.
[0025] 2. The movement of polymer chains is restricted by controlling the addition ratio of bamboo powder and rape straw husk powder. The synergistic effect of the compounding of the two powders promotes the effective dispersion of fibers, reduces the agglomeration inside the material, and improves the uniformity and orderliness of the rice-plastic composite. Under the van der Waals interaction force, the storage modulus and glassy modulus of the rice-plastic composite increase, thereby improving its tensile strength and tensile modulus, thereby improving the thermal stability and tensile properties of the rice-plastic composite.
[0026] 3. Under the mixing and hot pressing state of the hot mixer, the molar ratio of MgO and MgSO4 in the magnesium oxysulfide cement is adjusted to increase the density of the Hesu composite material, so that the alkoxy groups contained in Konalink 101 react with the hydroxyl groups on the surface of the calcium carbonate nucleating agent to form chemical bonds, making the internal structure of the Hesu composite material more compact. The magnesium oxysulfide cement, coupling agent and calcium carbonate play a good synergistic role, improving its axial tensile strength and axial tensile elastic modulus, and greatly improving the axial tensile mechanical properties of the Hesu composite material.
[0027] 4. Change the pressure of the hot press extruder and the ratio of the composite foaming agent to fully mix the modified composite material with the composite foaming agent, reduce the diameter of the pores of the Hesu composite material while increasing the number of bubbles, and further improve the Shore hardness of the material. Improve the aging resistance of the material while reducing its moisture content, which has a positive effect on the water resistance of the Hesu composite material.
[0028] 5. The extrusion molding process and the temperature of the material in the barrel have a great influence on the foaming state of the extruded foam. The appropriate extrusion molding temperature and process allow the polymer and the foaming agent to play a synergistic role, achieve good coating of the modified composite material, reduce the contact between the filler and water, effectively reduce the water absorption rate of the material, and improve the water resistance of the Hesu composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a diagram showing the effects of the extrusion molding process and temperature of Examples 28-32 of the present invention and Comparative Example 9 on the water absorption expansion rate and water absorption rate of the Hesu composite. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Please refer to Table 1, Table 2, Table 3, Table 4, Table 5 and Figure 1 The present invention provides a ramie-plastic composite material and a preparation method thereof, and the technical scheme is as follows:
[0032] The substance information involved in the present invention is as follows:
[0033] MgO CAS: 1309-48-4; MgSO4 CAS: 7487-88-9; Ethylene-ethyl acrylate copolymer CAS: 9010-86-0; High-density polyethylene CAS: 9002-88-4; Polypropylene CAS: 9003-07-0; Polyvinyl chloride CAS: 9002-86-2; γ-aminopropyltriethoxysilane CAS: 919-30-2; Tetraisopropyl titanate CAS: 546-68-9.
[0034] The bamboo chips were waste from a bamboo tube processing plant in Jiuhua Town, Chizhou City, Anhui Province; and the rapeseed straw was selected from the farmland of Matang Village, Tianchang City, Chuzhou City, Anhui Province.
[0035] Example 1
[0036] The bamboo chips and rape straw were simply crushed by a crusher to obtain crushed bamboo chips and rape straw with a size of 1 cm; the crushed rape straw was sent to a density separator, and the suction head speed was adjusted to 2.1 mm / sec and the rotation speed was 20 rpm to separate the pith with lower density and the husk with higher density; the separated crushed rape straw husk and crushed bamboo chips were crushed again by a high-speed pulverizer, and bamboo chip powder (BFP) and rape straw husk powder (RSSP) with a mesh number of 60 were sieved and placed in a drying oven at 110°C to dry to constant weight.
[0037] Bamboo dust powder, rape straw husk powder and ethylene-ethyl acrylate copolymer were added to a hot mixer at a mass ratio of 70:30 together with 100 parts of EAA and 0.3 parts of magnesium oxysulfate cement. The molar ratio of H2O / MgSO4 in the ternary system of magnesium oxysulfate cement was set to 20 / 1, and the molar ratio of MgO to MgSO4 was 4:1. The speed of the hot mixer was adjusted to 500r / min and the temperature was 85℃. The mixture was fully mixed and stirred for 10min to achieve the melting of EAA, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material. 4 parts of KH-550 and 2 parts of calcium carbonate nucleating agent were added to the mixed material, and the high-speed rotation friction heat of the hot mixer tool was used for mixing and hot pressing. The modified composite material was obtained after mixing at a speed of 2500r / min and a temperature of 85℃ for 10min.
[0038] Take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder. Add a composite foaming agent and water as auxiliary agents and hot press for 5 minutes at 175°C, a rotation speed of 400r / min, and a pressure of 1MPa; the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 3-5:1; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite material.
[0039] The temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 195°C to fully foam it to obtain the primary material; the temperature in die zone II is reduced from 195°C to 140°C to prepare the Hesu composite material.
[0040] Embodiment 2-5
[0041] Different from Example 1, the suction head speed and rotation speed of the density separator are different, and other preparation parameters remain unchanged. The specific parameters are summarized in Table 1.
[0042] Embodiment 6-7
[0043] Different from Example 1, the sieve mesh numbers of the bamboo dust powder and the rape straw husk powder are different, and other preparation parameters remain unchanged. The specific parameters are summarized in Table 1.
[0044] Comparative Example 1
[0045] Different from Example 1, the rape straw powder is composed of crushed rape straw, and the pith and husk are not separated by a density separator. Other preparation parameters remain unchanged. The specific parameters are summarized in Table 1.
[0046] Experimental Example 1
[0047] The bending resistance of Hesu composites was tested with reference to GB / T 29418-2012, with a sample size of 150mm×50mm×5mm, a bending rate of 10mm / min, and a span of 100mm. The relevant data are summarized in Table 1.
[0048] Table 1 Effect of pretreatment parameters and pretreatment methods of raw materials on the bending properties of Hesu composites
[0049] Example Suction head speed / (mm / sec) Speed / rpm BFP, RSSP / target Bending strength / MPa Flexural modulus / MPa Example 1 2.1 20 60 37.61 2987.68 Example 2 4.2 20 60 49.04 3578.64 Example 3 6.4 20 60 43.26 3395.33 Example 4 4.2 40 60 58.27 3824.67 Example 5 4.2 60 60 65.34 4105.33 Example 6 4.2 60 80 76.23 4399.75 Example 7 4.2 60 100 68.72 4287.59 Comparative Example 1 0 0 80 17.10 1375.23
[0050] According to the results shown in Table 1, in Comparative Example 1, the raw material rape straw powder was prepared without separating the pith and the skin, and the crushed rape straw and the crushed bamboo chips were directly crushed by a high-speed grinder. The bending strength and bending modulus of the prepared grass-plastic composite were much lower than those of Examples 1-7; after being crushed by a high-speed grinder, the rape straw skin showed a regular strip shape during the crushing process, while the pith showed an irregular folded state; this is because lignin is concentrated in the skin of rape straw, while the lignin content in the pith is low; the presence of lignin The rape straw husk is given a better load-bearing ability, a supporting network is formed in the rice-plastic composite, and the overall rigidity of the rice-plastic composite is increased; at the same time, the interface compatibility with the bamboo powder fiber is enhanced, the bending strength and bending modulus of the rice-plastic composite are enhanced, and its bending resistance is improved; and the suction head speed and rotation speed of the density separator are adjusted in Examples 1-5, so that the rape straw husk and the rape straw pith are better separated, and purer rape straw husk fibers are obtained. The separated rape straw husk fibers are compatible with the bamboo powder fiber and the polymer. Enhanced, while being able to reduce the impact of impurities on the preparation process; after screening the particle size of bamboo powder and rape straw husk powder in Examples 5-7, it was found that with the continuous increase in the particle size, the bending strength and bending modulus of the rice-plastic composite both showed a trend of first increasing and then decreasing; this is because when bamboo powder and rape straw husk powder are used to fill the rice-plastic composite, the larger the particle size, the smaller the specific surface area, resulting in excessive internal voids, affecting the distribution and arrangement of fibers in the rice-plastic composite, which is not conducive to improving the bending resistance of the rice-plastic composite; and too large a particle size If the particle size is too small, it will lead to reduced interfacial bonding force inside the fiber and between the fiber and other materials such as polymers, and the surface roughness is too low, thus affecting the bending strength and bending modulus of the rice-plastic composite, and reducing its bending resistance; in Examples 5-6, as the particle size increases, the surface area increases, and the friction and contact area inside the material also increase accordingly, resulting in an increase in the viscosity of the system, forming a criss-cross skeleton structure inside the rice-plastic composite, the internal connection of the material is tighter, and the ability to resist bending deformation is stronger. The prepared rice-plastic composite has higher bending strength and bending modulus. Therefore, it is more appropriate that the particle size of bamboo powder and rape straw outer skin powder should be controlled at 80 mesh.
[0051] Example 8
[0052] The bamboo chips and rape straw were simply crushed by a crusher to obtain crushed bamboo chips and rape straw with a size of 1 cm; the crushed rape straw was sent to a density separator, and the suction head speed was adjusted to 4.2 mm / sec and the rotation speed was 60 rpm to separate the pith with lower density and the husk with higher density; the separated crushed rape straw husk and crushed bamboo chips were crushed again by a high-speed pulverizer, and bamboo chip powder (BFP) and rape straw husk powder (RSSP) with a mesh number of 80 were sieved and placed in a drying oven at 110°C to dry to constant weight.
[0053] Bamboo dust powder and rape straw husk powder were added to a hot mixer at a mass ratio of 70:30 together with 100 parts of EAA and 0.3 parts of magnesium oxysulfate cement. The molar ratio of H2O / MgSO4 in the ternary system of magnesium oxysulfate cement was set to 20 / 1, and the molar ratio of MgO to MgSO4 was 4:1. The speed of the hot mixer was adjusted to 500r / min and the temperature was 85°C. The mixture was fully mixed and stirred for 10 minutes to achieve the melting of EAA, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material. 4 parts of KH-550 and 2 parts of calcium carbonate nucleating agent were added to the mixed material, and the high-speed rotation friction heat of the hot mixer tool was used for mixing and hot pressing. The modified composite material was obtained after mixing at a speed of 2500r / min and a temperature of 85°C for 10 minutes.
[0054] Take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder. Add a composite foaming agent and water as auxiliary agents and hot press for 5 minutes at 175°C, a rotation speed of 400r / min, and a pressure of 1MPa; the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 3-5:1; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite material.
[0055] The temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 195°C to fully foam it to obtain the primary material; the temperature in die zone II is reduced from 195°C to 140°C to prepare the Hesu composite material.
[0056] Examples 9-10
[0057] The difference from Example 8 is that the ratio of bamboo chip powder to rape straw husk powder in the mixture is different, and other preparation parameters remain unchanged. The specific parameters are summarized in Table 2.
[0058] Examples 11-13
[0059] Different from Example 8, the type of polymer added to the mixed material is different, and other preparation parameters remain unchanged. The specific parameters are summarized in Table 2.
[0060] Comparative Example 2
[0061] Different from Example 8, no polymer was added to the mixed material, and other preparation parameters remained unchanged. The specific parameters are summarized in Table 2.
[0062] Comparative Example 3
[0063] Different from Example 8, only 70 parts of bamboo dust powder were added to the mixed material, and rape straw husk powder was not added. Other preparation parameters remained unchanged. The specific parameters are summarized in Table 2.
[0064] Experimental Example 2
[0065] The tensile properties of the PP-S composites were tested with reference to GB / T 29418-2012. The test results of the tensile properties of the PP-S composites are summarized in Table 2.
[0066] Table 2 Preparation parameters of mixed materials and test on tensile properties of prepared materials
[0067] Example BFP: RSSP / copy Polymer Type Tensile strength / MPa Tensile modulus / MPa Example 8 70:30 EAA 25.87 1208 Example 9 60:40 EAA 33.24 2043 Example 10 50:50 EAA 29.16 1364 Embodiment 11 60:40 HDPE 37.26 2129 Example 12 60:40 PVC 51.38 3762 Embodiment 13 60:40 PP 56.40 3874 Comparative Example 2 60:40 / 13.63 924 Comparative Example 3 70:0 PP 16.72 1153
[0068] As can be seen from Table 2, Examples 8-10 show different tensile strengths and tensile moduli in the tensile performance test table of the rice-plastic composite because of the different ratios of bamboo dust powder and rape straw husk powder added to the mixed material; the addition amount of bamboo dust powder and rape straw husk powder affects their movement, slip and orientation with the polymer molecular chain, restricts the growth of polymer crystals, and thus improves the creep resistance of the composite material; by controlling the addition ratio of bamboo dust powder and rape straw husk powder, the movement of the polymer chain is restricted, thereby improving the thermal stability and tensile properties of the rice-plastic composite. Bamboo chip powder has a natural fiber structure, and its powder contains high levels of cellulose, hemicellulose and lignin. These components play a role similar to that of steel bars in the preparation process of rice-plastic composites and can improve the tensile strength of the material; rapeseed straw husk powder contains more cellulose and lignin, which can also play a role in enhancing the tensile strength and tensile modulus of the material; appropriately increasing the proportion of bamboo chip powder added can improve the van der Waals interaction between bamboo chip powder and rapeseed straw husk powder and polymer, improve the storage modulus and glassy modulus of the rice-plastic composite, and at the same time improve its tensile strength and tensile modulus; the compounding of the two powders can produce a synergistic effect, which can improve the tensile properties of the rice-plastic composite more than using either powder alone.
[0069] In Examples 9 and 11-13, the types of polymers were screened, and it was found that when the polymer added in Example 13 was polypropylene, the tensile strength and tensile modulus of the prepared PP-S composite were the best, with a tensile strength of up to 56.40 MPa and a tensile modulus of up to 3874 MPa. This is because the main chain of polypropylene is a saturated chain composed of carbon atoms, each carbon atom is connected to a hydrogen atom, and the side chain is a methyl group. This arrangement promotes effective dispersion of fibers, reduces agglomeration within the material, and improves the uniformity and tensile properties of the PP-S composite. At the same time, polypropylene is a semi-crystalline polymer, and the crystalline region is a lattice structure formed by the arrangement of polymer chains. This lattice structure has a high density and order, and possesses high strength and stiffness, and can effectively improve the tensile properties of the PP-S composite. While in Example 9 and Example 11, ethylene-ethyl acrylate copolymer and HDPE were added as polymers respectively, and the tensile strength and tensile modulus of the prepared rice-plastic composites were significantly lower than those of the rice-plastic composites prepared by Example 13 using PP as the polymer; this is because EAA and HDPE are both high-toughness polymers, and their dimensional stability and heat resistance are not as good as PP, and there is no obvious yield point, resulting in relatively low tensile strength and tensile modulus of the prepared rice-plastic composites, which cannot effectively improve the tensile properties of the rice-plastic composites. In Comparative Example 2, no polymer was added, and the tensile strength and tensile modulus of the rice-plastic composites were measured to be only 13.63MPa and 3874MPa, indicating that the polymer, as a continuous phase in the preparation process, can bond biomass fillers such as sawdust powder and rape straw husk powder to form a unified rice-plastic composite with high mechanical strength, further proving that the bonding effect of the polymer is the key to the good tensile properties of the rice-plastic composites. In Comparative Example 3, only bamboo chip powder was added, and the tensile strength and tensile modulus of the prepared rice-plastic composite were also relatively poor, indicating that only adding bamboo chip powder would result in structural voids inside the composite material, and there would be many voids, which would seriously affect the overall density of the rice-plastic composite, thereby reducing its tensile and mechanical properties.
[0070] Embodiment 14
[0071] The bamboo chips and rape straw were simply crushed by a crusher to obtain crushed bamboo chips and rape straw with a size of 1 cm; the crushed rape straw was sent to a density separator, and the suction head speed was adjusted to 4.2 mm / sec and the rotation speed was 60 rpm to separate the pith with lower density and the husk with higher density; the separated crushed rape straw husk and crushed bamboo chips were crushed again by a high-speed pulverizer, and bamboo chip powder (BFP) and rape straw husk powder (RSSP) with a mesh number of 80 were sieved and placed in a drying oven at 110°C to dry to constant weight.
[0072] Bamboo dust powder and rape straw husk powder were added to a hot mixer at a mass ratio of 60:40 together with 100 parts of PP and 0.3 parts of magnesium oxysulfate cement. The molar ratio of H2O / MgSO4 in the ternary system of magnesium oxysulfate cement was set to 20 / 1, and the molar ratio of MgO to MgSO4 was 4:1. The speed of the hot mixer was adjusted to 500r / min and the temperature was 85°C. The mixture was fully mixed and stirred for 10 minutes to achieve the melting of PP, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material. 4 parts of KH-550 and 2 parts of calcium carbonate nucleating agent were added to the mixed material, and the high-speed rotation friction heat of the hot mixer tool was used for mixing and hot pressing. The modified composite material was obtained after mixing at a speed of 2500r / min and a temperature of 85°C for 10 minutes.
[0073] Take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder. Add a composite foaming agent and water as auxiliary agents and hot press for 5 minutes at 175°C, a rotation speed of 400r / min, and a pressure of 1MPa; the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 3-5:1; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite material.
[0074] The temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 195°C to fully foam it to obtain the primary material; the temperature in die zone II is reduced from 195°C to 140°C to prepare the Hesu composite material.
[0075] Examples 15-17
[0076] The difference from Example 14 is that the molar ratio of the added MgO to MgSO4 is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 3.
[0077] Examples 18-19
[0078] The difference from Example 14 is that the type of coupling agent added is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 3.
[0079] Examples 20-21
[0080] The difference from Example 14 is that the amount of calcium carbonate added is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 3.
[0081] Comparative Example 4
[0082] Different from Example 14, no coupling agent was added during the preparation of the modified composite material, and other preparation parameters were the same. The specific parameters are summarized in Table 3.
[0083] Comparative Example 5
[0084] Different from Example 14, no calcium carbonate nucleating agent was added during the preparation of the modified composite material, and other preparation parameters were the same. The specific parameters are summarized in Table 3.
[0085] Comparative Example 6
[0086] Different from Example 14, during the mixing and hot pressing process of the modified composite material preparation, the speed of the hot mixer was 500 r / min and the temperature was 50° C., and the other preparation parameters were the same. The specific parameters are summarized in Table 3.
[0087] Experimental Example 3
[0088] The axial tensile mechanical properties of Hesu composites were tested with reference to GB / T 29418-2012; the relevant data are summarized in Table 3.
[0089] Table 3 Effect of adjusting the preparation parameters of modified composite materials on the axial tensile mechanical properties of Hesu composites
[0090] Example <![CDATA[MgO:MgSO4]]> Coupling agent type Calcium carbonate / part Axial tensile strength / MPa Axial tensile elastic modulus / MPa Embodiment 14 4:1 KH-550 2 7.28 3245.63 Embodiment 15 6:1 KH-550 2 8.45 3562.26 Example 16 8:1 KH-550 2 8.69 3824.74 Embodiment 17 10:1 KH-550 2 9.87 4168.23 Embodiment 18 10:1 KR55 2 9.04 3928.64 Embodiment 19 10:1 Konalink101 2 10.17 4228.87 Embodiment 20 10:1 Konalink101 4 10.89 4459.22 Embodiment 21 10:1 Konalink101 6 10.56 4374.65 Comparative Example 4 10:1 / 4 3.41 1345.52 Comparative Example 5 10:1 Konalink101 / 2.59 967.83 Comparative Example 6 10:1 Konalink101 4 5.23 2689.95
[0091] As shown in Table 3, in Examples 14-17, as the molar ratio of MgO to MgSO4 increases, the measured axial tensile strength and axial tensile elastic modulus also increase. When the molar ratio of MgO to MgSO4 is 10:1, the axial tensile strength of the tested Hesu composite is 9.87MPa, and the axial tensile elastic modulus is 4168.23MPa. Because the solubility of MgSO4 in water is low, the solubility at 20°C is only 33.7g. Therefore, the molar ratio of H2O / MgSO4 is set to 20 / 1 to ensure that MgSO4 can be completely dissolved in water, and the optimal mix ratio for preparing the ternary system magnesium oxysulfide cement is achieved by changing the content of active MgO. Examples 17-19 and Comparative Example 4 explored the effects of adding different coupling agents and not adding coupling agents on the axial tensile mechanical properties of the rice-plastic composite. The alkoxy groups contained in the monoalkoxyaluminate coupling agent Konalink 101 used in Example 19 reacted with the hydroxyl groups on the surface of the calcium carbonate nucleating agent to form chemical bonds, making the internal structure of the rice-plastic composite more compact and improving its axial tensile strength and axial tensile elastic modulus. In Comparative Example 4, no coupling agent was added, and the axial tensile mechanical properties of the obtained rice-plastic composite were significantly reduced. Examples 19-21 and Comparative Example 5 explored the effects of the number of calcium carbonate nucleating agents added and not adding calcium carbonate on the axial tensile mechanical properties of the rice-plastic composite. The measured results showed that excessive calcium carbonate would cause the composite material to become brittle and the bubbles to collapse, while too little or no calcium carbonate would not be enough to provide sufficient strength for the rice-plastic composite, which is not conducive to improving the axial tensile mechanical properties of the rice-plastic composite. For Comparative Example 6, due to the decrease in temperature and rotation speed of the hot mixer, it is difficult for magnesium oxysulfate cement, coupling agent and calcium carbonate to play a good synergistic role, resulting in a significant decrease in the axial tensile mechanical properties of the prepared Hesu composite.
[0092] Embodiment 22
[0093] The bamboo chips and rape straw were simply crushed by a crusher to obtain crushed bamboo chips and rape straw with a size of 1 cm; the crushed rape straw was sent to a density separator, and the suction head speed was adjusted to 4.2 mm / sec and the rotation speed was 60 rpm to separate the pith with lower density and the husk with higher density; the separated crushed rape straw husk and crushed bamboo chips were crushed again by a high-speed pulverizer, and bamboo chip powder (BFP) and rape straw husk powder (RSSP) with a mesh number of 80 were sieved and placed in a drying oven at 110°C to dry to constant weight.
[0094] Bamboo dust powder and rape straw husk powder were added to a hot mixer at a mass ratio of 60:40 together with 100 parts of PP and 0.3 parts of magnesium oxysulfate cement. The molar ratio of H2O / MgSO4 in the ternary system of magnesium oxysulfate cement was set to 20 / 1, and the molar ratio of MgO to MgSO4 was 10:1. The speed of the hot mixer was adjusted to 500r / min and the temperature was 85°C. The mixture was fully mixed and stirred for 10 minutes to achieve the melting of PP, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material. 4 parts of Konalink 101 and 2 parts of calcium carbonate nucleating agent were added to the mixed material, and the high-speed rotation friction heat of the hot mixer tool was used for mixing and hot pressing. The modified composite material was obtained after mixing at a speed of 2500r / min and a temperature of 85°C for 10 minutes.
[0095] Take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder. Add a composite foaming agent and water as auxiliary agents and hot press for 5 minutes at 175°C, a rotation speed of 400r / min, and a pressure of 1MPa; the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 3:1; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite material.
[0096] The temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 195°C to fully foam it to obtain the primary material; the temperature in die zone II is reduced from 195°C to 140°C to prepare the Hesu composite material.
[0097] Embodiment 23-24
[0098] The difference from Example 22 is that the pressure of the hot pressing extruder is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 4.
[0099] Examples 26-27
[0100] Different from Example 22, the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 4.
[0101] Comparative Example 7
[0102] Different from Example 22, only sodium bicarbonate endothermic foaming agent is added to the composite foaming agent, and other preparation parameters are the same. The specific parameters are summarized in Table 4.
[0103] Comparative Example 8
[0104] The difference from Example 22 is that only azodicarbonamide exothermic foaming agent is added to the composite foaming agent, and other preparation parameters are the same. The specific parameters are summarized in Table 4.
[0105] Experimental Example 4
[0106] The water resistance of the Hesu composite was tested with reference to GB / T 29418-2012. The moisture content of the Hesu composite is the ratio of the weight of the water contained in the Hesu composite to the total weight of the Hesu composite, which reflects the moisture content of the Hesu composite and is an important indicator for evaluating the performance and stability of the material. The sample size of 260mm×260mm×260mm was prepared by the preparation method shown in Example 22. The measurement results of the water resistance of the obtained Hesu composite are summarized in Table 4.
[0107] Table 4 Effect of changing the hot press extruder pressure and the ratio of composite foaming agent on the water resistance of Hesu composites
[0108] Example Pressure / MPa <![CDATA[NaHCO3:AC]]> <![CDATA[Density / (g / m 3 )]]> Shore Hardness Moisture content / % Embodiment 22 1 3:1 0.93 68 1.27 Embodiment 23 2 3:1 1.06 76 1.05 Embodiment 24 3 3:1 0.95 62 1.31 Embodiment 25 2 3:1 1.12 83 0.76 Embodiment 26 2 4:1 1.13 84 0.73 Embodiment 27 2 5:1 1.19 89 0.33 Comparative Example 7 2 5:0 0.73 56 2.53 Comparative Example 8 2 0:1 0.64 47 3.56
[0109] According to Table 4, in Examples 22-24, as the pressure of the hot press extruder continued to increase, the density and Shore hardness of the Hesu composite showed a trend of first increasing and then decreasing, and the water content of the material first decreased and then increased; under the pressure conditions of Example 23, the modified composite material and the composite foaming agent were fully mixed, the pore diameter of the Hesu composite was reduced while the number of bubbles was increased, the Shore hardness of the material was further improved, the aging resistance of the material was improved while its water content was reduced, and the water resistance of the Hesu composite was positively affected. In Example 25-26, the mass proportion of sodium bicarbonate endothermic foaming agent is increased, and the density change rate of the Hesu composite is small, and its Shore hardness and moisture content changes are basically kept stable; in Example 25-27, the mass of the exothermic azodicarbonamide foaming agent is not changed, and the mass proportion of the endothermic sodium bicarbonate foaming agent is increased. It is measured that the density of the Hesu composite prepared in Example 27 is significantly increased compared with that in Example 25-26, and its Shore hardness can reach 89, and the moisture content is as low as 0.33%; under the preparation conditions of this ratio, the endothermic sodium bicarbonate foaming agent is heated and decomposed when passing through the mouth mold zone I and the core mold zone I, absorbs heat and generates gas, and prevents the foaming from being too large due to excessive temperature; when passing through the mouth mold zone II and the core mold zone II, the temperature needs to be lowered again, and the exothermic azodicarbonamide foaming agent is thermally decomposed and releases heat and gas, which prevents the temperature from dropping too fast, resulting in the formation of shrinkage holes in the center of the material, and the bubbles are not dense and uniform. In Comparative Examples 7-8, only sodium bicarbonate endothermic foaming agent and azodicarbonamide exothermic foaming agent were added respectively. The density of the Hesu composite was significantly lower than the density of the material added with the composite foaming agent in Example 27, which further confirmed that the combination of endothermic and exothermic foaming agents can balance the temperature changes in the foaming process, improve the cushioning and mechanical properties of the material, and thus optimize the water resistance of the Hesu composite.
[0110] Embodiment 28
[0111] The bamboo chips and rape straw were simply crushed by a crusher to obtain crushed bamboo chips and rape straw with a size of 1 cm; the crushed rape straw was sent to a density separator, and the suction head speed was adjusted to 4.2 mm / sec and the rotation speed was 60 rpm to separate the pith with lower density and the husk with higher density; the separated crushed rape straw husk and crushed bamboo chips were crushed again by a high-speed pulverizer, and bamboo chip powder (BFP) and rape straw husk powder (RSSP) with a mesh number of 80 were sieved and placed in a drying oven at 110°C to dry to constant weight.
[0112] Bamboo dust powder and rape straw husk powder were added to a hot mixer at a mass ratio of 60:40 together with 100 parts of PP and 0.3 parts of magnesium oxysulfate cement. The molar ratio of H2O / MgSO4 in the ternary system of magnesium oxysulfate cement was set to 20 / 1, and the molar ratio of MgO to MgSO4 was 10:1. The speed of the hot mixer was adjusted to 500r / min and the temperature was 85°C. The mixture was fully mixed and stirred for 10 minutes to achieve the melting of PP, magnesium oxysulfate cement, bamboo dust powder and rape straw husk powder to obtain a mixed material. 4 parts of Konalink 101 and 2 parts of calcium carbonate nucleating agent were added to the mixed material, and the high-speed rotation friction heat of the hot mixer tool was used for mixing and hot pressing. The modified composite material was obtained after mixing at a speed of 2500r / min and a temperature of 85°C for 10 minutes.
[0113] Take 100 portions of the modified composite material and place them on a stainless steel pad, manually lay them into blanks, and then put them into a hot press extruder. Add a composite foaming agent and water as auxiliary agents and hot press for 5 minutes at 175°C, a rotation speed of 400r / min, and a pressure of 2MPa; the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent in the composite foaming agent is 5:1; the added amounts of the composite foaming agent and water account for 5% and 3% of the total mass of the Hesu composite material.
[0114] The temperature of the extruder barrel in the transition body and die zone I is rapidly increased from 175°C to 195°C to fully foam it to obtain the primary material; the temperature in die zone II is reduced from 195°C to 140°C to prepare the Hesu composite material.
[0115] Examples 29-30
[0116] The difference from Example 28 is that the temperature of the die zone I is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 5.
[0117] Examples 31-32
[0118] The difference from Example 28 is that the temperature of the die zone II is different, and the other preparation parameters are the same. The specific parameters are summarized in Table 5.
[0119] Comparative Example 9
[0120] Different from Example 28, the rapid heating process is not performed in the die zone I, and other preparation parameters are the same. The specific parameters are summarized in Table 5.
[0121] Experimental Example 5
[0122] The water resistance of Hesu composites was tested with reference to GB / T 29418-2012; water absorption thickness expansion rate: the specimen was immersed in a constant temperature water tank, the water temperature was maintained at 20°C, and the thickness change of the specimen before and after water absorption was measured; the water absorption thickness expansion rate is the ratio of the thickness increase after water absorption to the thickness before water absorption; the water absorption rate is expressed by the weight of water absorbed per unit volume of the material; the water absorption rate is usually used to evaluate the dimensional stability and water resistance of artificial board products, and is an important indicator for measuring the dimensional change of the material after water absorption; the preparation method shown in Example 28 was used to prepare a specimen with a size of 50mm×50mm×50mm, and the immersion time was 65d; the relevant data are summarized in Tables 5 and Figure 1 middle.
[0123] Table 5 Effect of extrusion molding process on water resistance of Hesu composites
[0124]
[0125]
[0126] As shown in Table 5 and Figure 1As shown, Examples 28-32 and Comparative Example 9 adjusted the extrusion molding process of the Hesu composite and the temperatures of the die zone I and the die zone II. After the adjustment, it was found that in Example 32, when the temperature of the die zone I was 195°C and the temperature of the die zone II was 160°C, the water resistance of the extruded Hesu composite was the best, the water absorption thickness expansion rate was 0.24%, and the water absorption rate was 1.37%; for Comparative Example 9, the material was not subjected to a rapid heating process when passing through the die zone I. After melting, the Hesu composite directly passed through the guide channel into the die zone II for finalization. The absorption thickness expansion rate and water absorption rate were significantly higher than those of the Hesu composite prepared in Examples 28-32; this is because the Hesu composite prepared without the rapid heating process of the die zone I has a significantly lower flow rate The viscosity and hardness of the material will also be affected by the temperature, which will greatly reduce the water resistance of the Hesu composite. The data of Examples 28-32 and Comparative Example 9 show that the extrusion molding process and the temperature of the material in the barrel have a great influence on the foaming state of the extruded foam. If the temperature is too low, the foaming agent will not be decomposed enough and the density of the final product will be too high. If the temperature is too high, the foaming agent will decompose too much in the barrel, the mechanical properties of the product will decrease, and the foaming gas will easily pass through the melt surface, resulting in an increase in surface porosity. The appropriate extrusion molding temperature and process allow the polymer and the foaming agent to play a synergistic role, achieve good coating of the modified composite material, reduce the contact between the filler and water, effectively reduce the water absorption rate of the material, and improve the water resistance of the Hesu composite.
[0127] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a grass-plastic composite material, characterized in that: The preparation method is as follows: The crusher is used to simply crush bamboo chips and rape straw to obtain crushed bamboo chips and crushed rape straw with a size of 1 cm; the crushed rape straw husk and the crushed rape straw pith in the crushed rape straw are separated by a density separator with a suction head speed of 2.1-6.4 mm / sec and a rotation speed of 20-60 rpm; the crushed rape straw husk and the crushed bamboo chips are crushed again, and sieved to obtain bamboo chip powder and rape straw husk powder with a mesh number of 60-100 meshes; The bamboo dust powder and the rape straw husk powder are added to a hot mixer according to a mass ratio of 50-70:30-50, together with a polymer and magnesium oxysulfide cement, and stirred for 10 minutes to obtain a mixed material; a coupling agent and 2-6 parts of a calcium carbonate nucleating agent are added to the mixed material, and the mixed material is kneaded and hot-pressed by utilizing the high-speed rotation friction heat of the hot mixer, and mixed at a speed of 2500 r / min and a temperature of 85° C. for 10 minutes to obtain a modified composite material; 100 portions of the modified composite material are put into a hot press extruder, and a composite foaming agent and water are added as auxiliary agents for hot pressing for 5 minutes at 175°C and 1-3MPa; the temperature of the extruder barrel in the transition body and the die zone I is 175-220°C to obtain a primary material; the temperature in the die zone II is reduced from 195°C to 140-160°C to prepare a Hesu composite material; The mass ratio of the endothermic foaming agent to the exothermic foaming agent in the composite foaming agent is 3-5:1; the endothermic foaming agent is sodium bicarbonate; the exothermic foaming agent is azodicarbonamide; the added amounts of the composite foaming agent and the water account for 5% and 3% of the total mass of the Hesu composite material.
2. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The pretreatment process of the bamboo dust powder and the rape straw husk powder is as follows: using a crusher to simply crush bamboo dust and rape straw to obtain the crushed bamboo dust and the crushed rape straw with a size of 1 cm; sending the crushed rape straw into the density separator, adjusting the suction head speed and the rotation speed of the density separator to separate the crushed rape straw pith with a smaller density and the crushed rape straw husk with a larger density; using a high-speed pulverizer to crush the separated crushed rape straw husk and the crushed bamboo dust again, sieving them, and then putting them into a 110°C drying oven to dry to constant weight to obtain the bamboo dust powder and the rape straw husk powder with a mesh size of 60-100 meshes.
3. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The suction head speed of the density separator is 4.2-6.4 mm / sec, and the rotation speed is 40-60 rpm; the sieving mesh number of the bamboo scraps powder and the rape straw husk powder is 80-100 meshes.
4. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The polymer is any one of ethylene-ethyl acrylate copolymer, high-density polyethylene, polypropylene and polyvinyl chloride.
5. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The mass ratio of the bamboo scraps powder to the rape straw husk powder is 50-60:40-50.
6. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The preparation method of the magnesium oxysulfate cement is as follows: MgSO4 and H2O in a molar ratio of 1:20 are stirred and H2SO4 with a purity of 98% is slowly added to dissolve to obtain a mixture one, MgO is added to the mixture one, the molar ratio of the added MgO to the MgSO4 is 8-10:1, and stirring is continued for 5 minutes to obtain the magnesium oxysulfate cement.
7. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The preparation method of the mixed material is as follows: adding the bamboo dust powder and the rape straw husk powder into the hot mixer at a mass ratio of 60:40 together with 100 parts of polymer and 0.3 parts of magnesium oxysulfide cement, adjusting the speed of the hot mixer to 500 r / min and the temperature to 85° C., fully mixing and stirring for 10 minutes to achieve melting of the polymer, the magnesium oxysulfide cement, the bamboo dust powder and the rape straw husk powder to obtain the mixed material.
8. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The coupling agent is any one of the silane coupling agent γ-aminopropyltriethoxysilane, the titanate coupling agent tetraisopropyl titanate, and the monoalkoxyaluminate Konalink101.
9. The method for preparing a grass-plastic composite material according to claim 1, characterized in that: The preparation method of the rice-plastic composite material is as follows: 100 portions of the modified composite material are placed on a stainless steel pad, manually laid into a blank, and then placed in the hot press extruder, and 5% of the composite foaming agent is added under the conditions of 175°C, a rotation speed of 400r / min, and a pressure of 1MPa, wherein the mass ratio of the sodium bicarbonate endothermic foaming agent to the azodicarbonamide exothermic foaming agent is 3:1; 3% of the water is added as an auxiliary agent and hot pressed for 5 minutes; the temperature of the extruder barrel in the transition body and the die I zone is rapidly increased from 175°C to 220°C to fully foam it to obtain the primary material; the temperature in the die II zone is reduced from 195°C to 140°C to prepare the rice-plastic composite material.
10. A rice-plastic composite material, characterized in that: The grass-plastic composite includes a modified composite material and a composite foaming agent; the modified composite material includes a mixed material, a coupling agent and a calcium carbonate nucleating agent; the composite foaming agent includes an endothermic foaming agent sodium bicarbonate and an exothermic foaming agent azodicarbonamide; the mixed material includes bamboo dust powder, rape straw husk powder, a polymer and magnesium oxysulfate cement; the magnesium oxysulfate cement includes MgO, MgSO4 and H2O; the grass-plastic composite is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Bamboo-based / thermoplastic plastic nanocomposite material
CN101880464B
A porous wood-plastic composite material and a preparation method thereof
CN116218247B